P110 SMILE: Sustaining Medical Education In a Lockdown Environment. Facilitator perceptions of a free online access medical education platform as an adjunct to the traditional undergraduate curriculum during lockdown. (8th April 2021) - Pascoe, John; Foster, Paul; Quddus, Muntasha; Kosti, Angeliki; Guest, Francesca; Stevens, Sian; Bamford, Richard; Coulston, James; Pascoe, John
Abstract: Introduction: SMILE is a free online access medical education (FOAMed) platform created by UK surgical trainees and a medical student. During lockdown SMILE delivered 200 lectures with student attendance as high as 1400, from both UK and overseas medical schools. We report facilitator perceptions of delivering FOAMEd via SMILE. Method: A questionnaire was sent to 77 facilitators covering preconceptions and post-session perceptions of FOAMed. Results: 61/77 responses were received from faculty of a range of medical and surgical specialties. Only 38% (23/61) had previously taught online. Engaging a large audience virtually was a common concern and 17% purposely made sessions less interactive than they would have done for face-to-face teaching: 95% (58/61) felt the technology was adequate to deliver sessions. 100% of facilitators appreciated the use of SMILE moderators to help bridge the gap between themselves and the audience 24% (15/61) of facilitators used applications such as mentimeter that they perceived as increasing their connectivity with large audiences. 100% felt that FOAMed would play a central role beyond Covid. Conclusions: In the times of Covid, where online medical education is becoming the new normal, we show facilitators feel comfortable with delivering FOAMed. We also discuss how facilitators maximized effectiveness in very large audiences.